Correlation between cytomorphology and acid fast bacilli positivity in tubercular lymphadenopathy in far Western Nepal: a hospital based study - Shreepaili, Ashok; Dhakal, Sushil (International Journal of Research in Medical Sciences, 2020)
Background: Tuberculous lymphadenitis is the most common manifestation of extrapulmonary tuberculosis. Fine needle aspiration cytology (FNAC) is a valuable tool in diagnosis of tubercular lymphadenitis. The present study aims to determine the prevalence of different cytomorphological patterns in fine needle aspiration cytology of tubercular lymph nodes and their correlation with Acid Fast Bacilli (AFB) positivity on Ziehi-Neelsen (ZN) Staining. Methods: Fine needle aspiration cytology of 274 cases diagnosed as tubercular lymphadenitis over a period of a year were reviewed. Cytomorphological patterns were categorized into three patterns. Pattern I: Epithelioid granuloma without necrosis, Pattern II: Epithelioid granuloma with caseous necrosis and Pattern III: Caseous necrosis only. Fischer Exact test was applied to correlate cytomorphological pattern and AFB positivity. Results: Tuberculous lymphadenitis was most frequent in age group 21-30 years (24.81%). Cervical lymph nodes were the most frequent lymph nodes involved (84.67%). Pattern I was the most common cytomorphological pattern observed (49.3%). Overall AFB positivity was 28.10%. Maximum AFB positivity was seen in pattern III (73.3%). Conclusions: FNAC is the simple, cost effective and minimally invasive tool to diagnose tuberculous lymphadenitis. Study of both cytomorphological pattern and ZN staining for AFB can improve the diagnostic accuracy.